Justicia restaurativa: construyendo un marco englobador para la paz - Carvajal Pardo, Alejandro (2023)
Justice is, basically, the management of vengeance. Is it possible, then, for peace and justice to be closely related? The constant war about statehood has become a global concern. The theoretical frameworks typical ly used to approach these issues are, in general, very simplistic. A better framework for these tasks could be provided by restorative justice, understood as a paradigm that sees justice as a concern of communities rebuilding themselves after episodes of v iolence, and does not see it as systematic revenge. Schools can be a propitious scenario for the incorporation of restorative justice into a broader political culture.